DAMPAK BULLYING, KEKERASAN DAN HATE SPEECH PADA ANAK: STUDI KASUS DI SMK SWASTA CARINGIN BOGOR, INDONESIA - Kholifatul Husna Asri; Luthfia Nuraini Rahman; Rahmatul Ummah (Jurnal Anifa: Studi Gender dan Anak, 2022)
Cases of bullying have many forms and kinds, ranging from physical to psychological. Bullying is a negative behavior that can result in a person being uncomfortable or injured and repeatedly occurs, characterized by an imbalance of power between the bully and the victim. The purpose of this study was to determine the impact of bullying on SMK children. The method used in this research is to use a qualitative research type with a case study approach. The subjects of this study were students of Private Vocational Schools in Caringin District, Bogor Regency. Data collection techniques were carried out through observation, interviews and documentation. From the results of research and findings in the field, the forms of bullying that occur are bullying by embarrassing friends, ridiculing deficiencies, demeaning, giving nicknames, disturbing, and saying harshly. The act of bullying experienced by the victim can have a negative impact, namely: First, mentally, it causes the victim to prefer to be alone, not to hang out with his friends. Second, emotional, which makes the victim disinterested in many things, characterized by being quiet, sensitive, suffering from fear of socializing and losing or declining self-confidence. Third, physically. Scars and the feeling of tiredness that is felt so that it become severe stress, making the victim have no appetite and often feel sick.